New directions in web data management 1 - Vakali, Athena 1963-.; Jain, L. C.; SpringerLink (Online service). (Berlin Heidelberg Springer, 2011)
This book addresses the major issues in the Web data management related to technologies and infrastructures, methodologies and techniques as well as applications and implementations. Emphasis is placed on Web engineering and technologies, Web graph managing, searching and querying and the importance of social Web.
Innovations and Trends in Web Data Management -- Massive Graph Management for the Web and Web 2.0.-Web Engineering and Metrics -- Modern Web Technologies -- Federated Data Management and Query Optimization for Linked Open Data -- Queries overWeb Services -- Towards Adaptively Approximated Search in Distributed Architectures -- Online Social Networks: Status and Trends -- Enhancing Computer Vision using the Collective Intelligence of Social Media.-From Extensional Data to Intensional Data: AXML for XML -- Migrating Legacy Assets through SOA to Realize Network Enabled Capability.
Electronic reproduction.
Keywords: Web databases; Database management; Electronic books